2012
DOI: 10.1002/mrc.3914
|View full text |Cite
|
Sign up to set email alerts
|

Chemical shifts of phenolic monomers in solution and implications for addition and self‐condensation

Abstract: Alkali metal counter-cations alter the electron density of phenolates in solution by electrostatic interactions. This change in electron density affects their reactivity toward formaldehyde, hydroxymethylphenols, and isocyanates during polymerization. The electronic perturbation of phenolic model compounds in the presence of alkali metal hydroxides was investigated with (13)C and (1)H nuclear magnetic resonance in polar solvents relative to non-ionic controls, altering the chemical shifts of the model compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…No 5aa′ was detected when Li 2 CO 3 was used or in the absence of any base. It is worth mentioning that the yields of 5aa′ by using different alkali metal carbonates in the reactions are consistent with their electron density ranking from 13 C NMR of the phenolic models in the literature, , which can be attributed to the different Coulombic interactions between the alkali metal cation and phenolate anion. These results demonstrated that the base additive plays a critical role in improving the reactivity and selectivity for para C–H functionalization of phenol with diazo compound in this dirhodium catalysis.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…No 5aa′ was detected when Li 2 CO 3 was used or in the absence of any base. It is worth mentioning that the yields of 5aa′ by using different alkali metal carbonates in the reactions are consistent with their electron density ranking from 13 C NMR of the phenolic models in the literature, , which can be attributed to the different Coulombic interactions between the alkali metal cation and phenolate anion. These results demonstrated that the base additive plays a critical role in improving the reactivity and selectivity for para C–H functionalization of phenol with diazo compound in this dirhodium catalysis.…”
Section: Resultssupporting
confidence: 81%
“…Accordingly, it was speculated that a facile formation of phenate intermediate from the free hydroxyl group and Cs 2 CO 3 might promote the para -selective C–H functionalization in this dirhodium catalysis. Published data show that, due to the electropositive character of the Cs + and the electron delocalization from the negatively charged oxygen to the aromatic ring, the electron density of the C4-carbon atom of phenolate is obviously increased as compared with 1a bearing the neutral OH group, thus enhancing the nucleophilic ability of the aromatic ring. To further evaluate this hypothesis, several commercially available alkali metal carbonates were tested as additives in the reaction of 1a and 2a (Scheme i). It was found that product 5aa′ was formed in 5–94% yields in the presence of Cs 2 CO 3, K 2 CO 3 , or Na 2 CO 3 .…”
Section: Resultsmentioning
confidence: 99%